2022
DOI: 10.1162/jocn_a_01807
|View full text |Cite
|
Sign up to set email alerts
|

Distributed and Multifaceted Effects of Threat and Safety

Abstract: In the present fMRI study, we examined how anxious apprehension is processed in the human brain. A central goal of the study was to test the prediction that a subset of brain regions would exhibit sustained response profiles during threat periods, including the anterior insula, a region implicated in anxiety disorders. A second important goal was to evaluate the responses in the amygdala and the bed nucleus of the stria terminals, regions that have been suggested to be involved in more transient and sustained … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 97 publications
5
19
0
Order By: Relevance
“…While the Region × Threat Certainty interaction was only marginally significant (p=0.10), focal comparisons indicated that that the Ce showed an indiscriminate pattern of reactivity, with statistically indistinguishable levels of heightened activation during the anticipation of certain and uncertain threat. In contrast, the BST showed preferential activation during the anticipation of uncertain threat, consistent with a recent large-scale (n=109) study that employed anatomical ROIs (Murty et al, 2022). These observations are broadly consistent with the influential model of Davis and colleagues-which suggests that the Ce is involved in responding to both kinds of threat-but run counter to the popular double dissociation model (Ce: Certain >> Uncertain ≈ 0;…”
Section: Kim Et Al Nicotine Abstinence Amplifies Withdrawal and Distr...supporting
confidence: 88%
“…While the Region × Threat Certainty interaction was only marginally significant (p=0.10), focal comparisons indicated that that the Ce showed an indiscriminate pattern of reactivity, with statistically indistinguishable levels of heightened activation during the anticipation of certain and uncertain threat. In contrast, the BST showed preferential activation during the anticipation of uncertain threat, consistent with a recent large-scale (n=109) study that employed anatomical ROIs (Murty et al, 2022). These observations are broadly consistent with the influential model of Davis and colleagues-which suggests that the Ce is involved in responding to both kinds of threat-but run counter to the popular double dissociation model (Ce: Certain >> Uncertain ≈ 0;…”
Section: Kim Et Al Nicotine Abstinence Amplifies Withdrawal and Distr...supporting
confidence: 88%
“…In an influential model, the BST was proposed to be engaged by diffuse threat, whereas the central amygdala was proposed to be engaged by immediate threat (Davis and Whalen, 2001). This purported dissociation has been challenged by some researchers (Gungor and Pare, 2016;Shackman and Fox, 2016;Fox and Shackman, 2019), but the precise contributions of the BST and the central amygdala to sustained versus phasic processes, respectively, remains unresolved (for examples in humans, see Hur et al, 2020;Murty et al, 2022).…”
Section: Circuits Involved In Anxiety-related Processingmentioning
confidence: 99%
“…Our finding of widespread and organized brainstem threat signaling calls for the abandonment of the historical division of labor view. In its place, we must embrace a brain-wide view of threat computation 36 38 in which brainstem networks are not limited to organizing fear behavior but are integral to estimating threat.…”
Section: Discussionmentioning
confidence: 99%